PENGARUH EFIKASI DIRI DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR EKONOMI DENGAN MOTIVASI BELAJAR SEBAGAI VARIABEL MEDIASI DI MASA PANDEMI COVID 19 - Laily Rochmah; Riza Yonisa Kurniawan (FKIP Unswagati, 2022)
AbstractDuring the Covid 19 pandemic, the learning process is limited online and offline so it has less time allocation than before. It was found that there were some students who cheated while doing assignments, daily tests and there were students who were less active in the class in the learning process. Quantitative research is correlational with the aim of knowing the effect of self-efficacy and learning environment with learning motivation as a mediating variable on economic learning outcomes. The sample of this research is the students of class X E5 and X E8 of SMAN 3 Sidoarjo with a total of 73 people. Primary data by distributing questionnaires while secondary data using the Final Semester Assessment. Data analysis using Structural Equation Modeling using WarPLS type 7.0 tool. The results of the discussion of observations show that self-efficacy directly affects learning motivation, self-efficacy has no effect on learning outcomes, learning environment affects learning motivation and learning outcomes, learning motivation affects learning outcomes. However, indirectly self-efficacy and learning environment cannot affect learning outcomes through learning motivation.Keywords: Self-Efficacy, Learning Environment, Learning Motivation